Short-wall paste continuous mining and continuous backfilling for controlling industrial square surface subsidence - Meng, Zixuan; Dong, Yue; Zhang, Xinguo; Jiao, Fangshu; Fan, Yaqi; Thammavongsa, Champa (Frontiers in Earth Science, 2023)
In order to facilitate coal mining under the industrial square in Western China, short-wall paste continuous mining and continuous backfill (PCMCB) is proposed to release overlaid resources and deal with the coal gangue. Firstly, the concept of short-wall PCMCB was presented, and the principle of surface subsidence was analyzed. Secondly, the mechanical model of the branch roadway and the strength of the backfill body was established by mechanical derivation. Thirdly, the proportion of backfill materials was calculated. Finally, the field application was carried out in the Dingjiaqu coal mine. The results show that: (1) Based on the simply supported beam model of the roof and the strength design model of the backfill body, a reasonable width of the branch roadway was determined to be 5m and the late strength of the backfill body should be more than 2.62MPa in the Dingjiaqu coal mine. (2) According to the design strength of the backfill body and the practice of backfill materials proportion, the reasonable proportion of cement: fly ash: gangue: water was determined to be 1:1.82:4.17:1.78. (3) In accordance with the equivalent mining height theory, in order to ensure that the deformation was within the first level of building damage, the critical filling rate of goaf should be more than 90%. (4) The field application shows that the subsidence could be controlled effectively by backfill, the overall surface subsidence was very small, and the maximum subsidence value (77mm) was far lower than the deformation extremes of the requirements of building protection. This paper provides practical experience for the exploitation of overlaid resources under similar shallow burial conditions. This scheme can help dispose the coal gangue with considerable social and economic benefits, which is worth popularizing and applying.